Cardiac tamponade and intracranial hemorrhage in a COVID-19 pediatric patient: Case Report: Taponamiento cardíaco y hemorragia intracerebral en un niño con la COVID-19: Reporte de un Caso - Rodríguez Portilla, Ricardo Enrique (2020)
The new coronavirus disease (COVID-19) is actually a pandemic according to the World Health Organization. It affects both the adult and pediatric population, however the most published information correspond to the first one, generating a knowledge gap regarding children. Pulmonary involvement appears to be the most frequently manifestation of the disease, although extrapulmonary complications such as pericardial effusion and cerebrovascular diseases have been reported in adults, and according to our review none have been reported in children. We present a case of a 7 year old patient with previous history of asthma and overweight that present COVID-19, and was admitted through the pediatric emergency department for pneumonia and developed a respiratory failure that requires ventilatory support. During its hospitalization presents cardiac tamponade and intracerebral hemorrhage with adverse evolution and fatal outcome.